2017
DOI: 10.18203/2394-6040.ijcmph20173360
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual problems among adolescent girls in Thiruvananthapuram district

Abstract: Background: Adolescence is a transitional stage extending from 10-19 years characterized by rapid physical, mental and sexual changes. It is also characterized by hormonal changes. As girls attain puberty at this age, they have various problems associated with menstruation. Menstruation is a natural phenomenon and an important indicator of women's health reflecting their reproductive function. However data on experiences of menstruation and it's impact on the health status, quality of life and social integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…[45,46] In this respect, Nazeema et al mentioned that the mean age at menarche varies from population to population and is known to be a sensitive indicator of various characteristics including geographical location, environmental conditions, nutritional status in society. [49] The present study has also revealed that more than half (58.7%) of the studied women had irregular menstruation and 78.0% of them suffered from oligomenorrhea. This corresponds well with Zandi et al, who reported that 59.4% and 61.3% of their studied subjects had irregular menstruation and oligomenorrhea.…”
Section: Discussionsupporting
confidence: 68%
“…[45,46] In this respect, Nazeema et al mentioned that the mean age at menarche varies from population to population and is known to be a sensitive indicator of various characteristics including geographical location, environmental conditions, nutritional status in society. [49] The present study has also revealed that more than half (58.7%) of the studied women had irregular menstruation and 78.0% of them suffered from oligomenorrhea. This corresponds well with Zandi et al, who reported that 59.4% and 61.3% of their studied subjects had irregular menstruation and oligomenorrhea.…”
Section: Discussionsupporting
confidence: 68%
“…Menstrual disorders are common presentation in late adolescence (Omidvar, Amiri, & Bakhtiari, 2018, p. 698). Dysmenorrhea and oligomenorrhea are found to be the commonest of all menstrual disorders among young women (Beevi, Manju, Bindhu, & Haran, 2017, p. 2995Latha et al, 1997, p. 6). Most adolescents experiencing dysmenorrhea have primary dysmenorrhea, defined as painful menstruation in the absence of pelvic pathology (American College of Obstetricians and Gynecologists, 2018), whereas oligomenorrhea is common in adolescents due to fluctuating hormonal level.…”
Section: Discussionmentioning
confidence: 97%
“…5,6 It was comparable to a study by Beevi et al in Thiruvananthapuram district in India and in study of Singh et al conducted in Madhya Pradesh where it was 12.2 years and 12.5 years respectively. 2,7 Age of menarche is dependent on various factors including socioeconomic conditions, environment, genetic factors, and nutritional status of adolescent girls. Moreover, it is observed that age of menarche is decreasing with each passing year.…”
Section: Discussionmentioning
confidence: 99%
“…Those who attend school during menstruation, do not attend the outdoor activities. 2 Most of the girls who attend school do not take medication for any menstrual issues. There is a definite effect on concentration in school going adolescents during menstruation in studies, which may have direct or indirect consequences of school drop out of such girls.…”
Section: Introductionmentioning
confidence: 99%